Partial nephrectomy: the benefits of advancing technology. (December 2014) - Bretterbauer, Katharina Maria; Hruby, Stephan; Lusuardi, Lukas; Colleselli, Daniela; Kunit, Thomas; Janetschek, Günter; Mitterberger, Michael
Open, laparoscopic and robot-assisted approaches are all feasible in partial nephrectomy and every procedure has its own pros and cons. Nowadays, open nephron-sparing surgery is the gold standard treatment of T1 renal cell cancer. In experienced centers, the laparoscopic or robot-assisted approach is a viable alternative. Advances in surgery and imaging techniques provide plenty of potential. With these new technical developments, it is possible to achieve zero ischemia of the kidney in a high percentage of cases, which has a positive effect on long-term renal function outcome. The purpose of this review is to discuss these new developments, which provide improvements to the partial nephrectomy procedure.